Homogeneous Catalytic Ozonation of Lipids Involving Fe2+ and Mn2+: An Experimental and Modeling Study. Issue 7 (21st June 2020) - Ramos, Rúbia Martins Bernardes; Biz, Ana Paula; Tavares, Deolinda Alvarez; Kolicheski, Mônica Beatriz; Dantas, Tirzhá Lins Porto
Abstract: Given the issue of lipids in effluent treatment systems and their negative impact on the environment, this study aimed to examine lipid degradation by homogenous catalytic ozonation with the aid of iron and manganese ions. This technology presents the possibility of completely mineralizing pollutants using hydroxyl radicals. Milk is chosen as the lipid source because of the high concentration of triglycerides in its matrix, this kind of lipid being the one found most frequently in food and, consequently, in effluent treatment systems. The milk pH value is controlled, and acidic, neutral, and basic conditions are evaluated. The rates of pseudo‐first‐order reactions and the effective value are estimated. It is shown that under acidic conditions low catalyst dosages are enough to cause the complete degradation of lipids. Under neutral conditions, a similar behavior is observed. Under basic conditions, higher catalyst dosages give higher reaction rates. The order of effectiveness of the catalysts under acidic and basic conditions is Fe 2+ > Mn 2+, with Mn 2+ > Fe 2+ under neutral conditions. Homogeneous catalytic ozonation is therefore efficient at lipid degradation. This technique is viable economically, since the lipid removal occurred at low ozone levels. In addition, the ions used as catalysts are naturally abundant. Abstract : Lipids in wastewater have attracted attention due to difficulties in their full mineralization in conventional wastewater treatments. Homogeneous catalytic ozonation is a promising technique for lipid degradation. Experimental evidence suggests that this technique is efficient in lipid degradation and is viable economically due to low ozone dosage and short reaction times, and the ions used are naturally abundant.